Predicting the severity of acute bronchiolitis in infants: Should we use a clinical score or a biomarker?. Issue 11 (27th December 2013) - Amat, Flore; Henquell, Cécile; Verdan, Matthieu; Roszyk, Laurence; Mulliez, Aurélien; Labbé, André
<x xml:space="preserve">Abstract</x> Krebs von den Lungen 6 antigen (KL‐6) has been shown to be a useful biomarker of the severity of Respiratory syncytial virus bronchiolitis. To assess the correlation between the clinical severity of acute bronchiolitis, serum KL‐6, and the causative viruses, 222 infants with acute bronchiolitis presenting at the Pediatric Emergency Department of Estaing University Hospital, Clermont‐Ferrand, France, were prospectively enrolled from October 2011 to May 2012. Disease severity was assessed with a score calculated from oxygen saturation, respiratory rate, and respiratory effort. A nasopharyngeal aspirate was collected to screen for a panel of 20 respiratory viruses. Serum was assessed and compared with a control group of 38 bronchiolitis‐free infants. No significant difference in KL‐6 levels was found between the children with bronchiolitis (mean 231 IU/mL ± 106) and those without (230 IU/mL ± 102), or between children who were hospitalized or not, or between the types of virus. No correlation was found between serum KL‐6 levels and the disease severity score. The absence of Human Rhinovirus was a predictive factor for hospitalization (OR 3.4 [1.4–7.9]; P = 0.006). Older age and a higher oxygen saturation were protective factors (OR 0.65[0.55–0.77]; P < 0.0001 and OR 0.67 [0.54–0.85] P < 0.001, respectively). These results suggest that in infants presenting with bronchiolitis for the first time, clinical outcome depends more on the adaptive capacities of the host than on epithelial dysfunction intensity. Many of the features of bronchiolitis are affected by underlying disease and by treatment. J. Med. Virol. 86:1944–1952, 2014. © 2013 Wiley Periodicals, Inc.